2019
DOI: 10.1021/acssuschemeng.9b05184
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylglycine-Betaine-Based-Catalyst-Promoted Novel and Ecocompatible Pseudo-Four-Component Reaction for Regioselective Synthesis of Functionalized 6,8-Dihydro-1′H,5H-spiro[[1,3]dioxolo[4,5-g]quinoline-7,5′-pyrimidine]-2′,4′,6′(3′H)-trione Derivatives

Abstract: Nowadays, synthesis of novel nitrogen-bearing heterocyclic scaffolds is a challenging and also demanding task. In our present work, we demonstrate a novel one-pot pseudofour-component reaction of 3,4-methylenedioxyaniline, N,Ndimethylbarbituric acid, and aryl/heteroaryl aldehydes for the regioselective construction of functionalized 6,8-dihydro-1′H,5H-spiro [[1,3]dioxolo[4,5-g]quinoline-7,5′-pyrimidine]-2′,4′,6′(3′H)-trione scaffolds using a trimethylglycine-betainebased sustainable catalyst. The title derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…As far as environmental sustainability is a concern, it is necessary to validate the present protocol with wellestablished "Green metrics" such as E-factor, Atom economy, Reaction mass efficiency, Effective mass yield, and Optimum efficiency. [38,39] The E-factor is a widely used green metric for the chemical reactions. The lower the value of the E-factor, the more eco-compatible reaction is.…”
Section: Resultsmentioning
confidence: 99%
“…As far as environmental sustainability is a concern, it is necessary to validate the present protocol with wellestablished "Green metrics" such as E-factor, Atom economy, Reaction mass efficiency, Effective mass yield, and Optimum efficiency. [38,39] The E-factor is a widely used green metric for the chemical reactions. The lower the value of the E-factor, the more eco-compatible reaction is.…”
Section: Resultsmentioning
confidence: 99%
“…This aerobic oxidative procedure offers a valuable utilization of simple alkyl azide derivatives 111 in N -heterocycle synthesis with nitrogen and water as co-products ( Scheme 27C ). High atom efficiency and good functional group tolerance make this procedure suitable in accessing numerous functionalized quinazolines (Patel and Patel, 2019 ).…”
Section: Transition Metal-catalyzed Methodologiesmentioning
confidence: 99%
“…Fluorescence investigation suggested that the synthesized quinazolines exhibit potent fluorescence properties with high quantum yield. These quinazolines have been proposed to be employed as a high fluorescent probe (Patel and Patel, 2019). Parua et al developed nickel [Ni(MeTAA)]-catalyzed approach for the formation of quinazoline derivatives 126 from acceptor-less dehydrogenative coupling of 2-aminobenzylamines 22 with benzyl alcohols 125 and 2-aminobenzylalcohols 88 with benzonitriles 127 in the presence of potassium tertbutoxide in xylene at 100 • C for 24 h (Parua et al, 2018).…”
Section: Nickel-mediated Catalytic Systemsmentioning
confidence: 99%
“…[7][8][9][10] 1,4-Dihydropyridines (as nitrogen-containing heterocycles) with a structure analogous to nicotinamide adenine dinucleotide (NAD) coenzyme have attracted considerable interest due to their different biological and medicinal applications. [7,[11][12][13][14][15][16][17][18][19][20][21] They have increasingly-popular worldwide applications such as antitumor, antisclerotic, antidiabetic, calcium channel blockers, anti-inflammatory, and analgesic. [22] Literature studies clearly show that they also have anti-TB activity owing to their lipophilic groups and can be used in tumor and Alzheimer's disease therapy as well.…”
Section: Introductionmentioning
confidence: 99%
“…1,4‐Dihydropyridines (as nitrogen‐containing heterocycles) with a structure analogous to nicotinamide adenine dinucleotide (NAD) coenzyme have attracted considerable interest due to their different biological and medicinal applications [7,11–21] . They have increasingly‐popular worldwide applications such as antitumor, antisclerotic, antidiabetic, calcium channel blockers, anti‐inflammatory, and analgesic [22] .…”
Section: Introductionmentioning
confidence: 99%